Training models for meniscal repairs and small joint arthroscopy. Issue 9 (16th March 2015) - Kovac, Nikola; Grainger, Nicholas; Hurworth, Mark
Abstract Background The reduced availability of human cadavers and their associated high costs, coupled with an increasing requirement for meeting continuing professional development targets, has accentuated the need for alternative training models that meet current ethical standards. The aim of this study is to identify suitable substitutes that are accessible and cost effective for use as training models for meniscal repairs and small joint arthroscopy. Method Ovine, bovine and porcine stifles were analysed for comparable anatomy to the human knee, arthroscopic access, arthroscopic view and ease of meniscal repair. Results The bovine stifle joint was found to be too large and offered limited access due to a large anterior fat pad and thick surrounding soft tissue. The ovine and bovine stifles were both easily available and had comparable anatomy to the human knee. Advantages of the porcine stifle include better availability and easier accessibility, comparable anatomy to the human knee and its relatively larger size that made it easier to arthroscope. Conclusion Porcine stifles are cost effective, accessible, allow for meniscal repair and are suitable for arthroscopic access and view. Our view is that they are an ideal training model for arthroscopic meniscal repair, small joint arthroscopy and anterior cruciate ligament reconstruction.